2019
DOI: 10.1109/access.2018.2885918
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Mobile Crowd-Sensing and Its Applications in the IoT Era

Abstract: The statements made herein are solely the responsibility of the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 133 publications
0
36
0
3
Order By: Relevance
“…Finally, it is worth noting that, with the rise of IoT [45,46], crowdsourcing is gaining momentum in a wide range of sectors and tasks [47,48,49,50,51]. In healthcare, crowdsourcing has been mainly employed to accomplish problem solving, data processing, surveillance/monitoring, and surveying [52], but there are not many mobile crowdsourcing applications [11,53] and even less decentralized while focused on healthcare [48].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, it is worth noting that, with the rise of IoT [45,46], crowdsourcing is gaining momentum in a wide range of sectors and tasks [47,48,49,50,51]. In healthcare, crowdsourcing has been mainly employed to accomplish problem solving, data processing, surveillance/monitoring, and surveying [52], but there are not many mobile crowdsourcing applications [11,53] and even less decentralized while focused on healthcare [48].…”
Section: Related Workmentioning
confidence: 99%
“…Different works on crowd sensing have shown that, in the IoT era, there are a multitude of data sources that can be successfully exploited in order to monitor crowds [40,41]. These different data sources are the main object of this section.…”
Section: Technologies and Data For Crowd Sensingmentioning
confidence: 99%
“…This is due to improved localization and reduced computational complexity, as concluded by Amr et al [ 19 ]. A detailed comparison of technologies and algorithms implementing the fingerprint technique for IoT indoor positioning has been carried out by [ 15 , 21 , 22 , 23 ].…”
Section: Related Workmentioning
confidence: 99%